Building Illustrative Drawing Competences in Students Based on the Principle Of Membership - Askarali Sulaymanov; Sarvar Tursunmuratovich Sobirov (Academia One Publishing, 2023)
The article describes the didactic requirements, content and methodology of organizing illustrative drawing lessons for students at the final stage of visual art education, and the technologies of using visual and expressive tools and techniques. Also, in this process, the stages of art education, the details of the use of coherence procedures between types and genres of visual art are presented
Keywords: pictorial activity; illustrative painting; type